Prospek Pemberantasan Korupsi: Perimbangan Kewenangan KPK dengan Institusi Penegak Hukum - Jawahir Thontowi (Unisia, 2008)
This study repeals that thet law enforcement on corruption crime carried by the Corruption Committee (KPK) cannot effectively control to minimize it from happening. It is important to take into account to propose that KPK still maintain to be established, but it role needs to be reduced in order to make a balance authority in handling corruption case between KPK and other legal institutions. In order to avoid conflict interest between involved parties police, public prosecutor and judges at district government level have their own jurisdiction to proceed corruption crime which are carried out by  public civil gervants. Hence, the establishment of Police Task Force inrespect to investigate corruption case is a vital role to take into consideration.